Use of RNALater® Preservation for Virome Sequencing in Outbreak Settings - Kohl, Claudia; Wegener, Merle; Nitsche, Andreas; Kurth, Andreas (Frontiers in Microbiology, 2017)
Abstract (50) Outbreaks of infectious diseases may occur in animal and human populations; this underlines the need for suitable One Health approaches. During outbreak situations, straightforward identification of etiological agents is indispensable for taking countermeasures. A recently published protocol for metagenomic virus detection in clinical specimens (TUViD-VM) was developed for snap-frozen tissues which can be challenging to obtain. Here, we describe the use of RNALater®-treated tissue at ambient temperatures for virome sequencing. This study demonstrates that samples stored in RNALater®buffer yield similar results to those stored snap-frozen.